Carrying Capacity of Govind Wildlife Sanctuary (and National Park), Uttarkashi District - Goyal, C. P.; Brahma, B. C. (Indian Forester, 2001)
One of the methods used for visitor management in a Protected Area is the concept of 'Carrying Capacity', which is the maximum use of any site which, if exceeded will result in the deterioration of the resource base. The present paper evaluates Physical Carrying Capacity (PCC = Visitors per day) and the Real Carrying Capacity (RCC = Visitors per day) for Govind Wildlife Sanctuary (and National Park) situated in Uttarkashi District of Uttaranchal. Govind Wildlife Sanctuary (and National Park) houses endangered fauna such as Snow Leopard, Brown and Black Bear, Musk Deer etc. Ten significant routes used by people within the Protected Area have been chosen for the study. On an average, 1323 visitors visit the Protected Area in a year during the tourist season, PCC represents a parameter that the ecosystem can withstand under static conditions. RCC is the capacity under restrictive condition. Two routes, Dhaula-Changsil (AMP =101; RCC = 98) and Motor - Kedarkanatha (AMP = 101; RCC = 89) the AMP has exceeded the threshold of RCC. Steep slopes increase erosion and landslides, local carts and cattle wi]] also use the roads besides tourists. Therefore, while managing reserved areas for ecodiversity and tourism, acceptable change factor should be considered while deciding their parameters.